2010
DOI: 10.1016/j.sigpro.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Implementation aspects of list sphere decoder algorithms for MIMO-OFDM systems

Abstract: a b s t r a c tA list sphere decoder (LSD) can be used to approximate the optimal maximum a posteriori (MAP) detector for the detection of multiple-input multiple-output (MIMO) signals. In this paper, we consider two LSD algorithms with different search methods and study some algorithm design choices which relate to the performance and computational complexity of the algorithm. We show that by limiting the dynamic range of log-likelihood ratio, the required LSD list size can be lowered, and, thus, the complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In this equivalent real system model, the QAM constellation can be viewed as two PAM constellations, and the matrix dimension is hence doubled. In [29], the real model was revealed to be more efficient for the implementation of the sphere decoder and it will be used for the system model in this paper.…”
Section: Turbo Principlementioning
confidence: 99%
See 1 more Smart Citation
“…In this equivalent real system model, the QAM constellation can be viewed as two PAM constellations, and the matrix dimension is hence doubled. In [29], the real model was revealed to be more efficient for the implementation of the sphere decoder and it will be used for the system model in this paper.…”
Section: Turbo Principlementioning
confidence: 99%
“…In [26], the tuple search detector (TSD) was introduced to improve the trade-off between STS-SD and LSD. Furthermore, soft versions of K-Best decoder and FSD decoder for iterative receiver were proposed in [27][28][29] and [30], respectively. The implementation of MIMO detectors have also been widely discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For a few good examples, refer to [24][25][26][27][28]. For a few good examples, refer to [24][25][26][27][28].…”
Section: The Sphere Detector Algorithmmentioning
confidence: 99%
“…The complexity analysis of the SD algorithm has been thoroughly investigated by several researchers. For a few good examples, refer to [24][25][26][27][28]. It has been shown that the complexity of the SD algorithm is directly proportional to the number of lattice points explored.…”
Section: The Sphere Detector Algorithmmentioning
confidence: 99%
“…The scheme adjusts the processing requirements of the SD to the target-error-rate (TER) performance by changing the log-likelihood ratio (LLR) clipping value after evaluating (i.e., tracking) the provided BER performance. In [1], [2] the fundamental idea of tuning the SD complexity and the performance via LLR clipping is demonstrated via extensive simulations. However, no discussion has been made on how to practically set the LLR clipping value in order to adjust on-the-fly the receiver's processing requirements to the TER.…”
mentioning
confidence: 99%